Socio-Technical Innovation Bundles for Enhancing Women’s Resilience and Empowerment: A Case Study of Swayam Shikshan Prayog’s Women-led Climate Resilient Farming - Jadhav, Radheshyam; Mukopadhyay, Prama; Chadha, Deepali; Shaikh, Naseem; Goe, Kritika; Patil, Upmanyu; Gartaula, Hom N.; Puskur, Ranjitha (CGIAR Initiative on Gender Equality, 2024)
The study explores how Socio-Technical Innovation Bundles (STIBs) integrated into SSP's WCRF model contribute to building the resilience and empowerment of women farmers in Dharashiv district in the region. By comprehending the dynamics and interaction of STIBS, it aims to contribute substantively to the discourse on empowering marginalized women farmers in the face of agrarian challenges and climate change impacts. The research methodology for the study revolves around axiological, ontological, and epistemological considerations, a research design that employs a constructivist/interpretivist paradigm, aligning with an inductive approach, and a qualitative approach to capture nuanced aspects of the research question. The study used purposive critical case sampling, semi-structured interviews, focus group discussions (FGDs), and a thematic analysis for data analysis. The cross-sectional time horizon provided a snapshot of prevalent characteristics within the population.